Growing Your Own: developing leaders through succession planning - Murray, Anne (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Few professions have spent as much time contemplating their present and future as have academic librarians. Conspicuous by its absence until recently has been any systematic discussion of leadership, and more specifically the process of succession planning. In this paper I will argue that neglect of succession planning reflects a series of widespread assumptions which, even if once valid, can no longer inform strategic planning for academic libraries. Although it is clear that there are risks attached to succession planning, the experience of Cambridge University Library highlights both the need for such an exercise and the advantages that it can bring to the profession of academic librarianship as a whole.